Novel cross-talk between IGF-IR and DDR1 regulates IGF-IR trafficking, signaling and biological responses - Malaguarnera, Roberta (Oncotarget, 2015)
The insulin-like growth factor-I receptor (IGF-IR), plays a key role in regulating mammalian development and growth, and is frequently deregulated in cancer contributing to tumor initiation and progression. Discoidin domain receptor 1 (DDR1), a collagen receptor tyrosine-kinase, is as well frequently overexpressed in cancer and implicated in cancer progression. Thus, we investigated whether a functional cross-talk between the IGF-IR and DDR1 exists and plays any role in cancer progression. Using human breast cancer cells we found that DDR1 constitutively associated with the IGF-IR. However, this interaction was enhanced by IGF-I stimulation, which promoted rapid DDR1 tyrosine-phosphorylation and co-internalization with the IGF-IR. Significantly, DDR1 was critical for IGF-IR endocytosis and trafficking into early endosomes, IGF-IR protein expression and IGF-I intracellular signaling and biological effects, including cell proliferation, migration and colony formation. These biological responses were inhibited by DDR1 silencing and enhanced by DDR1 overexpression. Experiments in mouse fibroblasts co-transfected with the human IGF-IR and DDR1 gave similar results and indicated that, in the absence of IGF-IR, collagen-dependent phosphorylation of DDR1 is impaired. These results demonstrate a critical role of DDR1 in the regulation of IGF-IR action, and identify DDR1 as a novel important target for breast cancers that overexpress IGF-IR.